Patrilineal genetic analysis of the origin of azaris of the Middle East - Vahid Rashidvash, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2013)
The origin of the Turkic-speaking population of the north-western provinces of Iran, the so-called Azaris, is the subject of long-year debate. Here, we present preliminary results on testing of several hypotheses concerning their origin: 1) the Azaris are the descendants of the Turkic ethnic groups migrated from Central Asia; 2) they have an autochthonous origins; 3) they are of Iranian origin; and 4) they have mixed ethnic origin with unknown proportions of source populations‟ contribution. The results show that Azaris have much weaker genetic affinity with the populations from Central Asia and the Caucasus than with their immediate geographic neighbours. Relying on these outcomes one can suggest that language replacement (change) with regard to Azaris occurred through “elite dominance” mechanism rather than “demic diffusion” model.